The Psychometric Properties of the Norwegian version of Revised Children´s Anxiety and Depression Scale (RCADS) - Elvsåshagen, Mari; Neumer, Simon-Peter; Eidet, Lise Mette; Lisøy, Carina (PsykTestBarn, 2024)
Description: The Revised Child Anxiety and Depression Scale (RCADS) is a self-report questionnaire developed by Chorpita and colleagues and translated to Norwegian by Marianne A. Villabø and Hanne Kristensen. The instrument has 47 or 25 items and is designed to assess clinical symptoms of anxiety and depression. There are four versions of RCADS, a short and long version for both parents and children. The test is available free of charge at rcads.ucla.edu. Literature search: Our systematic literature search identified 691 records after de-duplication. Of these, 14 articles fulfilled the inclusion criteria (2 Norwegian and 12 Swedish or Danish studies). The number of participants varied from 92 til 667. The children’s age was between 1 to 22 years. Five of the studies included their parents. Six studies concerned the general population, while two studies had a clinical group and a control group. Six studies focused mainly on clinical populations. Psychometrics: For the child version reliability was documented as internal consistency in nine studies for RCADS-47, and in two studies for RCADS-25. Three publications reported internal consistency for the parent version of RCADS-47. The scales vary from satisfying to excellent internal consistency in all publications. Several publications reported findings that supports RCADS´ construct validity. Mean scores were reported in 10 studies, but we did not find Scandinavian norm data. Criterion validity, Test-re-test-reliability or sensitivity to change was not documented in any publications. Conclusion: The psychometric properties for the Scandinavian full and short version of RCADS is adequate, and in line with findings from international studies. There is good evidence for psychometrics of both the short and long Child versions, however, there are not Scandinavian norms for either version. The Parent versions, however, need further research; there are no studies that detail psychometrics nor norms in a Scandinavian context.